Effective Permittivity of DMSO + NaCl Aqueous Solution as Influenced by Concentration and Temperature - Chen, Hai-Chuan; Yang, Xiao-Qing; Ma Huang, Ka (Asian Journal of Chemistry, 2013)
Dielectric properties of DMSO+NaCl aqueous solution were measured at the selected microwave frequency range (2.45 and 5.8GHz) by the open-ended coaxial probe method using a network analyzer. The effects of temperature (293-353K) and concentration (0.1-0.5 mol/L) on dielectric properties were investigated. Temperature and concentration significantly contributed on dielectric characteristics of DMSO dispersion and ion exhibited the electric conductivity dispersion effect.